Digital Marketing in Tourism Companies of the Central Region of Peru - Orihuela Ponciano, Andrea Soledad (2023)
The objective of the study was to determine the perception of the level of use of digital marketing in collaborators of tourism companies in the Central Region of Peru. The research approach was quantitative, the study design was non-experimental, cross-sectional, descriptive, the level of the research was descriptive, developed based on the perspective of Selman (2017)) which had 12 items, the dimensions were functionality flow, feedback and loyalty, the sample consisted of 13 tourism companies and 120 collaborators. The main result was that tourist establishments in the central regions of Peru make medium use of digital marketing as a business strategy.